Improvement of gastroesophageal reflux disease diagnostics in pediatrics - S. I. Erdes; A. R. Polischuk (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present data of the foreign clinical studies devoted to optimization of diagnostics of gastroesophageal reflux disease (GERD) in children.Key points. GERD is a frequent issue in pediatrics, its manifestations are difficult to reveal sometimes. In most of the cases gastroesophageal reflux (GER) is physiological, especially postprandially and can be detected in every child. Many episodes of refluxes proceed asymptomatically, however in some children GER is related to various serious symptoms and damage of esophageal mucosa because protective mechanisms are insufficiently developed in the young age. Therefore additional investigations are required to differentiate esophageal and extraesophageal manifestations of GERD. Multichannel intraluminal impedance — pH-metry is one of the modern diagnostic methods. It is very sensitive, allowing to reveal non-acidic, weakly acidic refluxes, as well as the height of refluxate spread.Conclusion. Multichannel intraluminal impedance measurement in comparison with intraesophageal pH-metry has wider diagnostic potentials as allows to determine episodes of acidic, non-acidic and alkaline refluxes.